Respuesta :
[tex]\bf \textit{Logarithm of rationals} \\\\ \log_a\left( \frac{x}{y}\right)\implies \log_a(x)-\log_a(y) \\\\[-0.35em] ~\dotfill\\\\ \log_3\left( \frac{c}{9} \right)\implies \log_3(c)-\log_3(9)[/tex]
Answer:
log3c-log3(9) i.e. [tex]log_{3}c-log_{3}9[/tex]
Step-by-step explanation:
As per logarithmic relation
[tex]log_{base}\frac{A}{B}=log_{base}A-log_{base}B[/tex]
Now, in the given question base value is 3. Therefore
[tex]log_{3}\frac{c}{9}=log_{3}c-log_{3}9[/tex]
Hence the correct answer is third option.